Algorithm generation for Rubik's cube via group theory for blindfold cubing - Montero, Jasper S. (2010)
This paper uses the permutation theory which closely related to Rubik's cube. The study aims to generate algorithms to be used in solving a Rubik's cube blindfolded. The method was a variation of the blindfold method discussed by Makisumi (2008) which used mainly 3 cycle algorithms. Concepts in group theory namely commutator, conjugation and order of the permutation were used in algorithm generation. Algorithm generation was done using trial and error method. Criteria were made to identify which generated algorithms were useful in blindfold cubing. Some algorithms generated in this study performed much better than some algorithms discussed by Makisumi (2008). Algorithms generated were then tested on a scrambled state of the cube.